The Influence of Competence, Independence, Professional Skepticism, and Audit Rotation (Study of public accountants throughout Indonesia) - Putra, Rheza Chandra; Rosdini, Dini; Irawady, Cahya (Universitas Pendidikan Indonesia, 2024)
The purpose of this research to determines the effect and correlation between Independent variable (X) that is Competence (X1), Independence (X2), Professional Skepticism (X3), and Audit Rotation (X4) to Dependent variable (Y) that is Audit Rotation (Y). Population of this research is All of Public Accountant in Indonesia. Sampling technique that used in this research was Cochran Sampling method. This research was obtained data from questionnaires that distributed to 238 Public Accountant in Bandung City, Centre Jakarta, West Jakarta, East Jakarta, North Jakarta, South Jakarta, and Bekasi City. Research method that used in this research was Path Analysis with SPSS 27 as statistics engine. The Results show that Competence (X1), Independence (X2), Professional Skepticism (X3), and Audit Rotation (X4) simulaneously has effect and correlation to Audit Rotation (Y).